2007
DOI: 10.5194/acp-7-3103-2007
|View full text |Cite
|
Sign up to set email alerts
|

A modeling analysis of a heavy air pollution episode occurred in Beijing

Abstract: Abstract. The concentrations of fine particulate matter (PM) and ozone in Beijing often exceed healthful levels in recent years, therefore China is to taking steps to improve Beijing's air quality for the 2008 Olympic Games. In this paper, the Models-3 Community Multiscale Air Quality (CMAQ) Modeling System was used to investigate a heavy air pollution episode in Beijing during 3-7 April 2005 to obtain the basic information of how heavy air pollution formed and the contributions of local sources and surround e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
49
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(50 citation statements)
references
References 7 publications
1
49
0
Order By: Relevance
“…Figure 6 illustrates the 24-h backward trajectory of the surface air mass arriving in Beijing at 17:00, which suggests that the photochemically-aged plume was associated with moderate southwesterly flows (∼300 km per day). The influences of the southerly transported polluted air mass on the air quality in Beijing have been discussed in previous studies (e.g., An et al, 2007, Wang et al, 2010b. The point underlined in this case study is that the coupling of in-situ photochemical ozone production during midday and the transport of ozone plumes in the late afternoon could further impact the air quality, particularly in terms of the "8-h-mean" O 3 guideline (WHO, 2006).…”
Section: Case 1: 3 August 2008mentioning
confidence: 58%
See 2 more Smart Citations
“…Figure 6 illustrates the 24-h backward trajectory of the surface air mass arriving in Beijing at 17:00, which suggests that the photochemically-aged plume was associated with moderate southwesterly flows (∼300 km per day). The influences of the southerly transported polluted air mass on the air quality in Beijing have been discussed in previous studies (e.g., An et al, 2007, Wang et al, 2010b. The point underlined in this case study is that the coupling of in-situ photochemical ozone production during midday and the transport of ozone plumes in the late afternoon could further impact the air quality, particularly in terms of the "8-h-mean" O 3 guideline (WHO, 2006).…”
Section: Case 1: 3 August 2008mentioning
confidence: 58%
“…Observations at a rural site showed that the monthly averaged daytime mixing ratio of O 3 for August 2008 was reduced by ∼20 %, as being compared with the same month of -2007(Wang et al, 2009b. However, comparing the observations in Beijing downtown for periods before and after the traffic control indicated an increase of 16 % in the mixing ratio of O 3 (Wang et al, 2010b).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Recently, An et al (2007) applied the CMAQ model to study a heavy particulate and sulfur episode observed in spring in Beijing by using emission switch on/off method, in his results, the contribution to the fine particles in Beijing was about 39 %∼53 % from the northwest (notably from Zhangjiakou), and 15 % from the southwest (notably from Baoding). Similarly, Streets et al (2007) reported that PM 2.5 concentrations from Shandong Province might reach a maximum contribution of 63 % to Beijing under certain Published by Copernicus Publications on behalf of the European Geosciences Union.…”
Section: Introductionmentioning
confidence: 99%
“…Especially in the most economically vibrant and densely populated areas, such as the Yangtze River Delta (YRD) region, the Pearl River Delta (PRD) region and the Beijing-Tianjin-Hebei (BTH) area, severe O 3 pollution episodes have frequently occurred (Lam et al, 2005; T. J. An et al, 2007;Chan and Yao, 2008;Duan et al, 2008;Jiang et al, 2008;Zhang et al, 2008;Guo et al, 2009;Shao et al, 2009;Ma et al, 2012), and the background air pollutant concentrations have steadily increased (Chan and Yao, 2008;Zhang et al, 2008;Tang et al, 2009;Ma et al, 2012;Liu et al, 2013). Many studies on the O 3 pollution, including satellite data analyses, field experiments and model simulations, have been carried out over China in order to investigate the temporal and spatial characteristics of surface photochemical pollution (Lu and Wang, 2006; H. X.…”
Section: Introductionmentioning
confidence: 99%